Pengembangan Sistem Informasi Penyewaan Gedung Graha Mustika Berbasis Android dan Web Terintegrasi Dengan Payment Gateway - Chalim, Noor; Setiawan, Rhoedy; Irawan , Yudie (Politeknik Negeri Media Kreatif, 2024)
This research focuses on developing an information system for the rental management of Graha Mustika Hall, located in Getaspejaten Village, Jati District, Kudus Regency. The venue is frequently utilized for various events; however, the existing rental process, including schedule management and payment confirmations, is handled manually. This method often results in recording errors and lacks transparency. The study aims to create a system accessible via Android and web platforms to simplify the rental process for both hall managers and tenants. Key features include real-time venue availability checks, rental request management, and payment gateway integration to streamline transactions. The system stores essential data such as rental rates, transaction details, tenant information, schedules, and equipment availability. The development process adopts the Extreme Programming methodology and utilizes UML for design. The system is expected to improve accuracy, transparency, and efficiency in managing Graha Mustika Hall, while also minimizing errors typically found in manual recording processes.